Do adverse pregnancy outcomes contribute to accelerated cardiovascular events seen in young women with systemic lupus erythematosus?. (November 2017) - Soh, M C; Nelson-Piercy, C; Westgren, M; McCowan, L; Pasupathy, D
Cardiovascular events (CVEs) are prevalent in patients with systemic lupus erythematosus (SLE), and it is the young women who are disproportionately at risk. The risk factors for accelerated cardiovascular disease remain unclear, with multiple studies producing conflicting results. In this paper, we aim to address both traditional and SLE-specific risk factors postulated to drive the accelerated vascular disease in this cohort. We also discuss the more recent hypothesis that adverse pregnancy outcomes in the form of maternal–placental syndrome and resultant preterm delivery could potentially contribute to the CVEs seen in young women with SLE who have fewer traditional cardiovascular risk factors. The pathophysiology of how placental-mediated vascular insufficiency and hypoxia (with the secretion of placenta-like growth factor (PlGF) and soluble fms-tyrosine-like kinase-1 (sFlt-1), soluble endoglin (sEng) and other placental factors) work synergistically to damage the vascular endothelium is discussed. Adverse pregnancy outcomes ultimately are a small contributing factor to the complex pathophysiological process of cardiovascular disease in patients with SLE. Future collaborative studies between cardiologists, obstetricians, obstetric physicians and rheumatologists may pave the way for a better understanding of a likely multifactorial aetiological process.